Herramientas lúdicas y su incidencia en el desarrollo de la motricidad gruesa en los estudiantes de segundo de la Escuela de Educación Básica Isidro Ayora del cantón Ventanas Provincia de Los Ríos - Pacheco Salvatierra, Dolores Xiomara (2016)
In the School of Basic Education "Isidro Ayora", of the Ventanas canton, Los Ríos province, it is evident that second-year students do not have gross motor skills, so the use of recreational tools is proposed, which they allow students to overcome the aforementioned problem. In this work several activities are presented where children in a fun way, perform multiple exercises in which they must use their muscles, maintain balance, and thus be able to achieve the development of gross motor skills. Among the benefits granted by the use of recreational tools, we find that students control body movements and improve their balance, this also allows them to develop their memory and intelligence and in the future fine motor skills are fully achieved